1998
DOI: 10.1029/98gb02738
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide fluxes in a northern fen during a hot, dry summer

Abstract: Atmospheric gradient techniques were used to measure the net ecosystem exchange of CO2 for a subarctic sedge fen near Churchill, Manitoba, during the summer of 1994. This was the second driest and wannest summer since 1943. The mean daily temperature was 2°C above average, and the rainfall was 55% below normal. More than half of the rain fell after the main growth period. The fen landscape comprises hummocks and hollows. Equilibrium retention storage occurs at an average standing water depth of 80 mm above the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…found that soil respiration increased in response to lowering water table, and several other studies have observed changes in wetland carbon balance from a net sink to a source during unusually warm, dry seasons (Shurpali et al, 1995;Schreader et al, 1998;Alm et al, 1999;Joiner et al, 1999;Bubier et al, 2003;Arneth et al, 2002). These studies reported short-term reductions in GEP attributed to water stress and early senescence, as well as temporary rises in ER or soil respiration.…”
Section: Discussionmentioning
confidence: 99%
“…found that soil respiration increased in response to lowering water table, and several other studies have observed changes in wetland carbon balance from a net sink to a source during unusually warm, dry seasons (Shurpali et al, 1995;Schreader et al, 1998;Alm et al, 1999;Joiner et al, 1999;Bubier et al, 2003;Arneth et al, 2002). These studies reported short-term reductions in GEP attributed to water stress and early senescence, as well as temporary rises in ER or soil respiration.…”
Section: Discussionmentioning
confidence: 99%
“…At the same fen in 1993, Burton et al (1996) found that ER was nearly three times higher during a dry period (18-29 July) than during a wet period (30 July -24 August) but the water level differences might have been more drastic than those that we observed. Similarly, a drought period in 1994 at the fen at Churchill was 2°C warmer and rainfall was 55% lower than normal so that the water table dropped 25-30 cm below the mean sedge-peat surface; this decreased NEE to only −0.05 g C m −2 day −1 during the peak growing period of 22 June -8 August (Schreader et al 1998). Rouse et al (2002) reported on five years of NEE for the fen at Churchill in the late 1990s and found that the years with the largest CO 2 uptake by the ecosystem had warmer-than-normal air temperature and normal to wetter-than-normal precipitation, which supports our observations during the 2011 study period.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…At a subarctic fen at Churchill, Manitoba, underlain by continuous permafrost, Burton et al (1996) reported that GPP and ER increased with warmer and drier conditions in late July compared to cooler and wetter conditions in early August of 1993. Schreader et al (1998) reported a net loss of 22 g C m −2 under unprecedented warm and dry conditions at the Churchill fen in the summer of 1994 (hottest and driest growing season in 50 years). They suggested that GPP was unaffected but ER increased during this year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warming is expected to increase evapotranspiration resulting in lower water tables that, in turn, will increase soil oxygen availability, microbial activity, and organic matter decomposition, reducing the Arctic's carbon sink potential (Schreader et al 1998). However, as a result of high spatial heterogeneity of the arctic landscape, differences in microtopography are likely to interact with temperature to control near the surface moisture changes (Engstrom et al 2005).…”
Section: Introductionmentioning
confidence: 99%